1996
DOI: 10.1111/j.1460-2695.1996.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF HYDROGEN ON THE FATIGUE BEHAVIOUR OF THE BETA‐TITANIUM ALLOY Ti‐3Al‐8V‐6Cr‐4Mo‐4Zr

Abstract: In order to characterize the influence of hydrogen on the mechanical properties of B-titanium alloys, monotonic tensile and straincontrolled fatigue tests were performed on samples of the metastable alloy Ti-3A1-8V-6Cr-4Mo-4Zr in uncharged (0.5 at.% hydrogen) and hydrogen-charged (3-4 at.% hydrogen) conditions. The hydrogen was introduced into the material during the last 8 h of an ageing treatment (28 h at 482°C) from the gas phase, whereas the reference (uncharged) specimens were annealed completely in vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This is also observed for the metastable b alloy Ti-3Al-8V-4Mo-4Zr (Christ et al, 1996), which showed loss in ductility on hydrogen charging, but no effect of hydrogen on the fatigue life. This apparent inertness to hydrogen effects in cyclic loading is baffl ing at fi rst glance.…”
Section: Hydrogen-enhanced Fatigue In Titanium Alloyssupporting
confidence: 63%
See 1 more Smart Citation
“…This is also observed for the metastable b alloy Ti-3Al-8V-4Mo-4Zr (Christ et al, 1996), which showed loss in ductility on hydrogen charging, but no effect of hydrogen on the fatigue life. This apparent inertness to hydrogen effects in cyclic loading is baffl ing at fi rst glance.…”
Section: Hydrogen-enhanced Fatigue In Titanium Alloyssupporting
confidence: 63%
“…A reasonable explanation for this phenomenon was not forthcoming. For a two-phase alloy the FCGRs for hydrogen and argon atmospheres were compared (Christ et al, 1996). No differences in the FCGRs were observed during elevated temperature testing, although signifi cant embrittlement due to hydrogen was observed at RT through tensile tests.…”
Section: Hydrogen-enhanced Fatigue In Titanium Alloysmentioning
confidence: 99%
“…Furthermore, dislocations are accelerated to overcome the barrier from other dislocations which results in cyclic softening. Similar cyclic softening behavior was also observed in Ti-3Al-8V-6Cr-4Mo-4Zr induced by the high density of dislocation in the a p particles [34]. The authors suggest that the homogeneous plastic deformation with sufficient stress or strain amplitude enables a rearrangement of dislocations and a relaxation of internal stress, and finally causes cyclic softening.…”
Section: Cyclic Hardening/saturation and Softening Behaviormentioning
confidence: 61%
“…Reports on the behavior of conventionally processed Ti-5553 on the macroscale differ from our observation, and they are not consistent: only cyclic softening, cyclic softening followed by saturation, or cyclic hardening followed by softening were observed. [12,42,43] Microstructural and compositional differences are one likely reason for the differences. All the reports refer to conventionally processed metastable β-alloys, with different compositions and heat treatments, compared to each other and our alloy.…”
Section: Cyclic Deformation and Creep Behaviormentioning
confidence: 99%